CASE STUDY OF LAHAT ROAD FAILURE SP AIR DINGIN KM 229 + 000 THE PLAXIS PROGRAM - Arfan, Muhammad; Anggraini, Nita (Universitas Muhammadiyah Palembang, 2018)
This study focuses on the study of sloop stability against the Lahat road segment SP Air Dingin KM. 229 + 000 considering that the landslide that occurred was quite steep. To find out the soil parameters, the researchers correlated the N-SPT data using the Rankin method and the PLAXIS 8.2 Program (Finite Element method). The researchers conducted VII modeling method I with the Safety Factor Value of 1.27, Model II with the Safety Factor value l, 55, Model III with Safety Factor 1.57, IV with Safety Factor 1.56, V with Safety Factor 1,28, VI with Safety Factor 1,72 and VII with Safety Factor 2,07. So the safest safety number for retening walls is in the VII model with a diameter of 80cm, a depth of 187, a safety factor value of 2.07.